2011 IEEE MTT-S International Microwave Symposium 2011
DOI: 10.1109/mwsym.2011.5972825
|View full text |Cite
|
Sign up to set email alerts
|

Over 10MHz bandwidth envelope-tracking DC/DC converter for flexible high power GaN amplifiers

Abstract: This paper describes a fast envelope-tracking circuit capable of 10 MHz (up to 17.5 MHz) bandwidth based on RF GaN switching devices and 50 MHz switching frequency. The efficiency of the VHF converter is 84% to 90% which is comparable to a conventional DCIDC converter for spaceborne application. A demonstrator has been built and mated with a RF GaN HEMT output stage. The CII measurement for lO-12W RF output power close to saturation show a linearity improvement by 5-8d8 and an efficiency improvement of up to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Additionally the third part of the driver is a resistive-load amplifier stage to amplify the signal from the output of the 2nd stage to drive the power stage. Compared to discrete converters which use bias tree to enlarge a driving signal in [14] and a hybrid gate driver in CMOS (Complementary Metal Oxide Semiconductor) [15], and integrated converters [10] with an external level shifter matching network, the proposed driver in this paper can be controlled directly by the CML level signal. The driver has less demand for a drivers' control signal and the 1st and 2nd stage can offer over a 4 V swing for the input of the 3rd stage.…”
Section: Driver Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally the third part of the driver is a resistive-load amplifier stage to amplify the signal from the output of the 2nd stage to drive the power stage. Compared to discrete converters which use bias tree to enlarge a driving signal in [14] and a hybrid gate driver in CMOS (Complementary Metal Oxide Semiconductor) [15], and integrated converters [10] with an external level shifter matching network, the proposed driver in this paper can be controlled directly by the CML level signal. The driver has less demand for a drivers' control signal and the 1st and 2nd stage can offer over a 4 V swing for the input of the 3rd stage.…”
Section: Driver Designmentioning
confidence: 99%
“…Then the size of the converter chips as well as the parasitic capacitance coming from the devices or introduced by the external package can be dramatically decreased. With discrete devices, Miguel R et al [9] illustrated a high efficiency demonstrator which can operate at 10-40 MHz switching frequency, Nicolas et al, reported a converter operating at 50 MHz with a preamplifier to amplify the control signal (after amplifying, the swing is 6.27 V) [14] and for a higher frequency range Ming-Jie et al demonstrated a converter that can operate at 300 MHz with an additional buffer for a control clock signal [15] but with low power density, i.e., 4.16 × 10 −6 W/mm 2 . To realize the monolithic integrated GaN based DC-DC converter and improve operating frequency, Zhang et al [10] used three circuit topologies at 100 MHz with a level shifter matching network to transmit the control signal (the swing is 5 V) generated by FPGA (Field Programmable Gate Array).…”
Section: Introductionmentioning
confidence: 99%
“…Fast transition converters are needed to track fast changing of power supplies voltage, e.g. envelopetracking power supplies for radio frequency power amplifiers (RFPA) [1][2][3]. The main issue of realizing the high operating frequency converter is the limitation of the Si-based power devices, but it is being solved after the advent of an advanced power device, such as GaN FET.…”
Section: Introductionmentioning
confidence: 99%
“…As modem telecommunications rely on higher data rates and are based on envelope-modulated signals featuring larger In this context, highly efficient DC/DC converters, capable of handling such bandwidths, are very attractive [4], [5].…”
Section: Introductionmentioning
confidence: 99%